ANALYSIS OF EFFECT OF SERVICE QUALITY IN MALL MANAGEMENT AND ITS RELATION TO TENANT SATISFACTION AT CENTER POINT MALL MEDAN - Radius Peranginangin; Sukaria Sinulingga; Prihatin Lumbanraja (Journal of Innovation Research and Knowledge, 2023)
The purpose of this research is to get empirical evidence of analysis of effect of service quality in mall management and its relation to tenant satisfaction at Center Point Mall Medan. This type of research is descriptive quantitative. This research will be conducted at Center Point Mall Medan. This research was conducted for 2 months, from April to May 2022. The number of space tenants currently occupied is 176 units which are the target population. The samples are tenants who are encountered when the observations are carried out at Center Point Mall Medan, namely 64 samples are taken using a random sampling technique. Methods of data analysis using multiple linear regression with partial (t) test. The results of the study show that tangible has a significant effect on tenant satisfaction at Center Point Mall Medan. Reliability has a significant effect on tenant satisfaction at Center Point Mall Medan. Responsiveness has a significant effect on tenant satisfaction at Center Point Mall Medan. Assurance has a significant effect on tenant satisfaction at Center Point Mall Medan. Emphaty has a significant effect on tenant satisfaction at Center Point Mall Medan.